Analysis of cytological activities in sugar beet calluses - Taha, R.M.; Ehsani-Moghaddam, B. (2008)
The present study focus on the results of cytological studies of embryogenic (E) and Non-Embryogenic (NE) calluses as the main tissues for cytological studies and the cells of primary root meristem derived from seedling or in vitro cloned plant, as reference tissues. The cellular parameters, such as Mitotic Index (MI), cell-doubling time (Cdt), cell and nuclear area and DNA C value of the different tissues, which may be involved with cell activity, have quantitatively been compared. Embryogenic callus of sugar beet, containing meristematic centers unlike the non-embryogenic one, the cytological behavior of their cells was very close to typical meristematic tissue i.e,, primary root of seedling. In non-embryogenic cells, increased in the rate of cytoplasm/nuclear (C/N) area, endoreduplication and reduction of mitotic index followed by increasing of cell doubling times were observed. Â© 2008 Asian Network for Scientific Information.